Wide Gastric Conduit Increases the Risk of Benign Anastomotic Stricture After Esophagectomy. Issue 6 (June 2020) - Zhu, Dong-shan; Cao, Jian-wei; Geng, Ming-fei; Huang, Xiao-yu; Hu, Chong-ming; Li, Jian; Fu, Dong-hong; Liu, Wei
Background: To identify the association between the width of the gastric conduit and the benign anastomotic stricture (BAS) after esophagectomy with end-to-side cervical anastomosis for esophageal cancer. Methods: Patients with esophageal cancer who underwent esophagectomy between July 2013 and July 2014 were included in this study. The gastric conduit was used for reconstruction in all patients and end-to-side cervical anastomosis were performed using a circular stapler. The patients were divided into a narrow group (3-5 cm) and a wide group (>5 cm) based on the gastric conduit width. Univariate and multivariate logistic regressions were used to analyze the possible factors (patients' age, gender, preoperative comorbidities, neoadjuvant chemotherapy, gastric conduit width, anastomotic leakage) that could affect the incidence of BAS. Results: Two-hundred and one patients were included in this study. The median follow-up period was 29 months (17-58 months). Seven cases (3.5%) showed anastomotic leakage in the postoperative period and 38 patients (18.9%) developed BAS; all within the first year of follow-up. In univariate analysis, the width of the gastric conduit was the only risk factor for the development of BAS (odds ratio [OR] = 3.36, P = .005). In multivariate logistic regression analysis, the wide group was an independent significant risk factor for the development of BAS developing compared with the narrow group (OR = 2.84, P = .02). Conclusions: A wide gastric conduit width (>5 cm) is an independent risk factor for the development of BAS after esophagectomy and stapled cervical end-to-side anastomosis for esophageal cancer.